Pemetaan Bibliometrik Kajian Search Engine Optimization (SEO) dalam Strategi Pemasaran Digital - Nur Hidayatul Istiqomah; Diana Nur Indah Purnamasari; Siswoyo (Al-Musthofa: Journal of Sharia Economics, 2025)
Digital transformation has fundamentally reshaped the marketing landscape, driving the adoption of technology-based strategies such as SEO to enhance online visibility and the effectiveness of marketing communication. However, as the number of scholarly publications discussing SEO within the context of digital marketing continues to grow, a systematic mapping is needed to understand the directions, trends, and patterns of research collaboration that are emerging. This study aims to conduct a bibliometric analysis of scientific literature examining SEO as part of digital marketing strategy. The method employed is a Systematic Literature Review (SLR) using the PRISMA approach, involving 27 articles published between 2019 and 2025. The analysis reveals that SEO occupies a central role in digital marketing discourse, closely linked to terms such as digital marketing strategy, website, and user engagement. Thematic clustering indicates a diversity of research approaches, covering technical, strategic, and conceptual dimensions. Temporal visualization also shows a significant increase in SEO-related publications in recent years, driven by its integration with technologies like machine learning and growing attention to user experience. In the context of Islamic economics, these findings open up opportunities to develop SEO strategies that are not only technically effective but also aligned with Sharia principles such as honesty, justice, and the promotion of halal products enabling digital marketing to be conducted ethically and contributing to the strengthening of the Islamic economic ecosystem in the digital realm.